Предмет: Алгебра,
автор: nevskya2004
Решите уравнение: (7х + 1)(x - 3) + 20(х - 1)(х + 1)= 3(3х - 2)2 + 13.
Ответы
Автор ответа:
0
(7х + 1)(x - 3) + 20(х - 1)(х + 1)= 3(3х - 2)2 + 13
7x²-21x+x-3+20(x²-1)=3(9x²-12x+4)+13
7x²-20x-3+20x²-20-27x²+36x-12-13=0
16x-48=0
16x=48
x=3
7x²-21x+x-3+20(x²-1)=3(9x²-12x+4)+13
7x²-20x-3+20x²-20-27x²+36x-12-13=0
16x-48=0
16x=48
x=3
Похожие вопросы
Предмет: Биология,
автор: maksimgrecanov82564
Предмет: Математика,
автор: catgop228
Предмет: Физика,
автор: genastrugov630
Предмет: Математика,
автор: катяlove2000
Предмет: Математика,
автор: veronika201698977